Learners' evaluation of HTML modules - Lim, Tick-Meng; Widad Othman; Woo, Tai-Kwan; Safiah Md Yusof; Halimatolhanin Mohd Khalid (2011)
A major step taken by OUM, as part of the continuous effort to improve its learning system and tools was the conversion of the print module, used primarily as resource for selfmanaged learning, into the web-based HTML modules. This paper describes the research which was conducted to evaluate the efficacy of OUM’s HTML modules from learners’ perspective. A set of questionnaire was prepared for the purpose. Subsequently a user evaluation survey was administered at OUM’s various learning centres. The analyses of the study indicate that HTML modules are generally well accepted by the learners. A t-test conducted indicates that the male learners rated the HTML modules higher than the female learners. Another Pearson correlation test shows that the ICT competency of the users has little effect on their perceived quality of the HTML modules, even though the modules are basically computer-based. Recommendations for improvements are proposed. (Abstract by authors)